Echocardiography study of right ventricular abnormalities in adult patients of sickle cell anaemia - Ahmad, Shakir; Toppo, Archana; Vanna, Sanjay (Journal of evolution of medical and dental sciences, 2017)
BACKGROUND Sickle Cell Disorder (SCD] is the first diagnosed disease that was linked to the haemoglobin protein. It is an autosomal recessive disorder that occurs throughout the world. The cardiac effects of this chronic illness on the left ventricle have been extensively investigated in adults. However, fewer adult studies and only one study that included adolescents have investigated any aspect of the impact of SCA on the Right Ventricle (RV). MATERIALS AND METHODS The study was conducted in the Department of Medicine, Dr. BRAM Hospital, Raipur, among the patients presenting in OPD and admitted in medicine ward. The study comprised of 138 patients with sickle cell anaemia. The age group chosen was between 14 years to 70 yrs. RESULTS Out of the total 138 cases, 84 (60.86%) were sickle cell trait (AS) and 54 (39.14%) were sickle cell disease (SS), Right Ventricular End Diastolic Area (RV-EDA), Right Ventricular End Systolic Area (RV-ESA), Right Ventricular Fractional Area Change (RV-FAC), Right Ventricular Free Wall Mass Index (RV-FWMI), Right Ventricular Rate Corrected Ejection Time (RV-Etc) was significantly higher in SS subjects compared to AS subjects. In our study group, 19 out of 58 (35.18%) patients of sickle cell disease had PH as compared to 13 out of 84 (15.47%) patients of sickle cell trait. CONCLUSION In our study, we have observed that various parameters which signify right ventricular abnormalities like increased systolic pulmonary pressure (sPAP), right ventricular end diastolic area, right ventricular end systolic area, right ventricular fractional area change, right ventricular free wall mass index and right ventricular ejection time (rate corrected) were found to be significantly higher in sickle cell disease patients (SS genotype) as compared to sickle cell trait patients (AS genotype). Also, the incidence and severity of anaemia was significantly higher in sickle cell disease patients (SS genotype). Moreover, increased incidence and severity of subsequent pulmonary hypertension correlates well with morbidity and mortality in these patients. KEYWORDS Echocardiography, Right Ventricle, Sickle Cell Anaemia.